2016
DOI: 10.5301/hipint.5000442
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Approach to Optimise Patient-Reported Outcome from Revision Hip Arthroplasty

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Abstract IntroductionMost total hip arthroplasty (THA) in the UK are performed through a posterior or lateral surgical approach. We aimed to investigate any difference in outcome from revision THA according to the approach at primary and revision THA surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…A surgical approach is a significant surgical choice both for primary [24, 25] and revision [2628] procedures, and should be based on several factors, such as previous approach, soft tissue and bone condition, and surgeon experience.…”
Section: Resultsmentioning
confidence: 99%
“…A surgical approach is a significant surgical choice both for primary [24, 25] and revision [2628] procedures, and should be based on several factors, such as previous approach, soft tissue and bone condition, and surgeon experience.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, there is no perfect approach. Posterolateral has been regarded as a preferred approach by individual authors as both the posterior column of the acetabulum and the femoral shaft can be addressed through the same 10) .…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies reporting the outcomes relative to the more common PL and MMH approaches in revision THA [ [13] , [14] , [15] , [16] ], and we were only able to locate one limited study reporting results using the ABMS approach for revision THA [ 17 ]. Shigemura et al.…”
Section: Discussionmentioning
confidence: 99%
“…grouped the surgical approach for primary THA with subsequent revision approaches to measure overall outcomes using the Western Ontario and McMaster Universities Arthritis Index and Oxford Hip Score scales [ 15 ]. They found that patients had better scores if they had a posterior approach for both their primary and revision THAs than when both primary and revision surgeries were performed in the lateral approach as well as a primary lateral approach and revision THA posterior approach [ 15 ]. In our study, there was no difference in outcome scores between approaches with respect to average change from baseline.…”
Section: Discussionmentioning
confidence: 99%